Systemic Antibiotics in Periodontal Treatment of Diabetic Patients: A Systematic Review. - Caroline Moura Martins Lobo Santos; Ronaldo Lira-Junior; Ricardo Guimarães Fischer; Ana Paula Pires Santos; Branca Heloisa Oliveira (PLoS ONE)
Aim To evaluate the effects of systemic antibiotics in combination with scaling and root planing (SRP) on periodontal parameters, tooth loss and oral health-related quality of life in diabetes patients. Materials and methods Two independent reviewers screened for controlled clinical trials with at least 6-month follow-up in six electronic databases, registers of clinical trials, meeting abstracts and four major dental journals. After duplicates removal, electronic and hand searches yielded 1,878 records; 18 full-text articles were independently read by two reviewers. To evaluate the additional effect of antibiotic usage, pooled weighted mean differences and 95% confidence intervals were calculated using a fixed effects model. Results Five studies met the inclusion criteria, four of which were included in meta-analyses. The meta-analyses showed a significant effect favouring SRP plus antibiotic for reductions in mean probing depth (PD) (-0.22 mm [-0.34, -0.11]) and mean percentage of bleeding on probing (BoP) (4% [-7, -1]). There was no significant effect for clinical attachment level gain and plaque index reduction. No study reported on tooth loss and oral health-related quality of life. Conclusion Adjunctive systemic antibiotic use in diabetic patients provides a small additional benefit in terms of reductions in mean PD and mean percentage of BoP. Registration Prospero CRD42013006389.